Direct Intra-Patient Comparison of Scaffold Protein-Based Tracers, [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE)3-G3, for Imaging of HER2-Positive Breast Cancer; Cancers; Vol. 15 - iss. 12 - Bragina O. D. Olga Dmitrievna; Chernov V. I. Vladimir Ivanovich; Shulga (Schulga) A. A. Aleksey Anatolievich; Konovalova E. V. Elena Valerjevna; Hober S. Sophia; Deev S. M. Sergey Mikhaylovich; Sorensen J. Jens; Tolmachev V. M. Vladimir Maksimilianovich (2023, 2023)
Previous Phase I clinical evaluations of the radiolabelled scaffold proteins [99mTc]Tc-ADAPT6 and DARPin [99mTc]Tc-(HE)3 -G3 in breast cancer patients have demonstrated their safety and indicated their capability to discriminate between HER2-positive and HER2-negative tumours. The objective of this study was to compare the imaging of HER2-positive tumours in the same patients using [99mTc]TcADAPT6 and [99mTc]Tc-(HE)3 -G3. Eleven treatment-naïve female patients (26–65 years) with HER2- positive primary and metastatic breast cancer were included in the study. Each patient was intravenously injected with [99mTc]Tc-ADAPT6, followed by an [99mTc]Tc-(HE)3 -G3 injection 3–4 days later and chest SPECT/CT was performed. All primary tumours were clearly visualized using both tracers. The uptake of [99mTc]Tc-ADAPT6 in primary tumours (SUVmax = 4.7 ± 2.1) was significantly higher (p < 0.005) than the uptake of [99mTc]Tc-(HE)3-G3 (SUVmax = 3.5 ± 1.7). There was no significant difference in primary tumour-to-contralateral site values for [99mTc]Tc-ADAPT6 (15.2 ± 7.4) and [99mTc]Tc-(HE)3-G3 (19.6 ± 12.4). All known lymph node metastases were visualized using both tracers. The uptake of [99mTc]Tc-ADAPT6 in all extrahepatic soft tissue lesions was significantly (p < 0.0004) higher than the uptake of [99mTc]Tc-(HE)3-G3. In conclusion, [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE)3-G3 are suitable for the visualization of HER2-positive breast cancer. At the selected time points, [99mTc]TcADAPT6 has a significantly higher uptake in soft tissue lesions, which might be an advantage for the visualization of small metastases.